Notes on the genus Neochauliodes from Guangxi, China (Megaloptera: Corydalidae) - Liu, Xingyue; Yang, Ding (Zootaxa, 2005)
The species of the genus Neochauliodes from Guangxi are reviewed. The following three species are described as new to science: Neochauliodes acutatus sp. nov., Neochauliodes fuscus sp. nov., and Neochauliodes nigris sp. nov. A key to the species from Guangxi is presented.